Inovasi Pembelajaran Hybrid Di Era Digital: Sinergi Metode Ceramah Dan Diskusi Dalam Praktik Pembelajaran - Suhupawati Suhupawati; M. Mahalli fikri; Winda Nur Wadi; Rido Fandika Agung; Isti Fitrah Ilmi (Alpatih Harapan Semesta, 2025)
The development of digital technology has driven a paradigm shift in school learning, including the implementation of hybrid learning as an effort to integrate offline and online learning. This study aims to describe the implementation of hybrid learning and analyze the synergy between lecture and discussion methods in learning practices at SMA Negeri 3 Selong. This study uses a qualitative approach with a descriptive method. Data collection techniques included learning observation, interviews with teachers, and documentation of learning activities. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that hybrid learning is implemented by combining face-to-face learning as the main activity and online learning as a support. The lecture method is used to convey basic concepts and build initial understanding among students, while the discussion method is used to increase participation and deepen understanding of the learning material. The synergy between the lecture and discussion methods creates a more focused, participatory, interactive, and meaningful learning process. Hybrid learning in this study is not only the use of technology, but also a pedagogical strategy in integrating learning methods in a balanced manner. The findings of this study show that proper planning and management of learning methods are the key to the success of hybrid learning in the digital age.